2007
DOI: 10.1645/ge-3519rn.1
|View full text |Cite
|
Sign up to set email alerts
|

Coprology of Panthera tigris altaica and Felis bengalensis euptilurus From the Russian Far East

Abstract: Fecal samples from the Siberian tiger (Panthera tigris altaica) and the Amur cat (Felis bengalensis euptilurus) from Far Eastern Russia, were examined for parasites. A natural sedimentation methodology was used and a complete examination of all the sediment was performed. This fecal investigation allowed us to isolate and identify several developmental stages of gastrointestinal, hepatic, and respiratory parasites. Five parasites were found from P. t. altaica: 11 trematodes (Platynosomum fastosum) and 4 nemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 21 publications
2
31
1
Order By: Relevance
“…The occurrence of T. cati in this species has already been reported by Fagiolini et al (2010) and Gonzalez et al (2007). Lion were infected with Toxascaris leonina, Spirometra sp.…”
Section: Discussionsupporting
confidence: 68%
“…The occurrence of T. cati in this species has already been reported by Fagiolini et al (2010) and Gonzalez et al (2007). Lion were infected with Toxascaris leonina, Spirometra sp.…”
Section: Discussionsupporting
confidence: 68%
“…Detailed morphometric studies (n=10) revealed the size of the eggs to be 81.78 ± 5.90 μm (74.8 -86.2 μm) × 65.8 ± 4.90 μm (57.0 -71.2 μm) (length × breadth). The results were in concordance with the fi ndings of Gonzalez et al (2007) and Okulewicz et al (2012), who reported T. leonina eggs with smooth walls and without any albuminous coat. The lions showed high egg per gram values (1033.33 ± 251.66, 1433.33 ± 251.66 and 783.33 ± 175.59) for T. leonina eggs before the therapeutic interventions during the three treatment schedules, which was further reduced with appropriate anthelmintics used (fenbendazole and ivermectin).…”
Section: Morphological Studies and Parasitic Intensity Assessmentsupporting
confidence: 92%
“…Aelurostrongylus abstrusus is a metastrongylide nematode parasite, which is known to infect the lungs of cats and other felids such as the Amur cat ( Felis bengalensis euptilurus ) (Gonzáles et al 2007) and the Eurasian lynx ( Lynx lynx ) (Szczesna et al 2006). This nematode is widespread and has been found repeatedly in almost all countries in Europe, frequently in Australia, several times in North and South America and sporadically in Asia and Africa.…”
Section: Introductionmentioning
confidence: 99%